Men and women writers of the 1930s : the dangerous flood of history - Montefiore, Jan (Routledge, 1996)
"Men and Women Writers of the 1930s is an original and important study of memory and gender in the literature of this tragic decade. Montefiore asks two principal questions: 'What part has memory played in the political literature of and about the 1930s?'and 'What were the roles of women, both as writers and as symbols, in constructing the literature?' ... Montefiore's analysis of issues such as mass unemployment, fascism, the tensions in pre-war Yugoslavia and 'appeasement' is shockingly relevant to society today. Anti-fascist historical novels, the post-war memoirs of 'Auden generation' writers, travel writing and neglected women poets are discussed at length"--Jacket